Disputando el poder de la fuerza con la ley: Los liberales en la temprana república peruana y la guerra civil de 1834 - Sobrevilla Perea, Natalia (Anuario de Historia de América Latina, 2021)
This article is interested in understanding the first generation of Peruvian liberals and the role they played in the creation of the first State institutions. They were the ones who designed the electoral systems, the constitutions and the judicial structures. From the first moment on they clashed with the military, which eventhough it claimed to respect the representative institutions, tended to look for ways to take over power and keep it by force. The liberals were convinced that with the power of the law, represented by the constitutions and the electoral processes, they created strong structures to prevail over the military force. Repeatingly clashing with the military, in 1834 the confrontations reached such heights that the people took the liberals’ side againts the military. But in the end this was a pyrrhic victory as a year later a new military revolution removed this first generation of liberals who never managed to regain access to power.
Keywords: Liberalism; Constitutionalism; Elections; Peruvian Independence